Italian Workers at Risk During the Covid-19 Epidemic - Teresa Barbieri; Gaetano Basso; Sergio Scicchitano (Global Labor Organization (GLO), 2020)
We analyse the content of Italian occupations operating in about 600 sectors with a focus on the dimensions that expose workers to contagion risks during the COVID-19 epidemics. To do so we leverage extremely detailed and granular information from ICP, the Italian equivalent of O*Net. We find that several sectors need physical proximity to operate: the workers employed in Italy in sectors whose physical proximity index is above the national average are more than 6.5 million (most of them in retail trade). Groups at risk of contagion and complications from COVID-19 (mainly male above the age of 50) work in sectors that are little exposed to physical proximity, currently under lockdown or can work remotely. The sectoral lockdowns put in place by the Italian Government in March 2020 seem to have targeted sectors who operate in physical proximity, but not those directly exposed to infections (the health industry is not subject to lockdown). Most workers who can operate from home have not been put under lockdown and are currently working. Therefore, the number of workers who are not in workplaces could be up to 3 million higher than those whose sector has been shutdown.
Keywords: J28; J81; H12; I18; 330; Working conditions; Safety; Crisis policies; COVID-19 epidemics